Fatores religiosos e os caminhos de associação com saúde bucal de adultos mais velhos e idosos do Brasil - Menegazzo, Gabriele Rissotto (2021)
Changes in the population pyramid stand out with a significant increase in older people all around the world. Knowing that psychosocial factors are linked to the determination of diseases, religious factors stand out in the literature for being important to aging. Despite the extensive development of these and health literature, little has been explored in relation to oral health. Therefore, the aim of this thesis was to evaluate the association between religious factors with the oral conditions of Brazilian older adults and olders and the paths that mediate this association through three articles, the first assesses the association between religious factors and oral health, measured objectively and subjectively, and the others assess the direct and indirect paths between religiosity and tooth loss, and between religiosity and oral health related quality of life (OHRQoL). For this, a cross-sectional view of the “Longitudinal Study of Health of the Elderly Brazilian” (ELSI-Brazil) was conducted and count with a representative sample of adults with 50 years-old or older from Brazil. Data collection took place between 2015 and 2016 and the measures evaluated were collected through questionnaires. The outcomes of this thesis were tooth loss, assessed by reporting the number of missing teeth, and OHRQoL, assessed using the Oral Impacts on Daily Performance questionnaire. To assess religious factors, spirituality was measured by the importance of religion in life, religious frequency through participation in ceremonies and religiosity through the report about having a religion and practicing it, in addition to which religion it belongs to. Statistical analysis used the statistical programs STATA 14 and Mplus version 6.12. Adjusted rates ratios were calculated using Poisson regression models. Afterwards, Structural Equation Models verified the paths that lead religiosity to outcomes. The ELSI-Brazil was approved by the National Research Ethics Committee of Brazil and its final sample size was 9,412 individuals. Individuals who reported having spirituality had a higher prevalence of worse OHRQoL and individuals who reported belonging to the Catholic, Evangelical or other religions had a lower prevalence of worse OHRQoL, when compared to those who reported not having a religion. Religious variables were not associated with tooth loss. However, it was observed that smoking was directly associated with worse oral health conditions and was a mediator of the relationship between lower religiosity and worse OHRQoL, through less social support. Poor oral hygiene also mediated this relationship, through less spirituality, via tooth loss. Furthermore, spirituality directly affected tooth loss and OHRQoL. In conclusion, religious factors are associated with OHRQoL in older adults and olders Brazilians and have an indirect protective effect against tooth loss and OHRQoL. This should be considered in oral health promotion and prevention planning, taking into account the relevance of the influences of psychosocial factors, integrating different community resources and allowing the development of common risk factor approaches.